Autophagy Activation Induces p62-Dependent Autophagic Degradation of Dengue Virus Capsid Protein During Infection - Wu, Yaoxing; Zhou, Tao; Hu, Jiajia; Liu, Yishan; Jin, Shouheng; Wu, Jianfeng; Guan, Xiangdong; Cui, Jun (Frontiers in Microbiology, 2022)
In the past decade, dengue virus infection is one of the most prevalent and rapidly spreading arthropod borne diseases worldwide with about 400 million infections every year. Although it has been reported that dengue virus could take advantage of autophagy to promote its propagation, the association between selective autophagy and dengue virus remains largely unclear. Here we demonstrated that dengue virus capsid protein, the key viral protein for virus assembly, maturation, and replication, underwent autophagic degradation after autophagy activation. Autophagy cargo receptor p62 delivered ubiquitinated capsid protein to autophagosomes for degradation, which could be enhanced by Torin 1 treatment. Further study revealed that the association between p62 and viral capsid protein was dependent on the ubiquitin binding domain of p62 and the poly-ubiquitin conjugated at lysine 76 of capsid protein served as a recognition signal for autophagy. Consistently, p62 deficiency in Huh7 cells led to the enhancement of dengue virus replication. Our study revealed that p62 targeted dengue virus capsid protein for autophagic degradation in a ubiquitin-dependent manner, which might uncover the potential roles of p62 in restricting dengue virus replication.